Tuning the Fermi-level of TiO 2 mesoporous layer by lanthanum doping towards efficient perovskite solar cells - Gao, Xiao-Xin; Ge, Qian-Qing; Xue, Ding-Jiang; Ding, Jie; Ma, Jing-Yuan; Chen, Yao-Xuan; Zhang, Bao; Feng, Yaqing; Wan, Li-Jun; Hu, Jin-Song (Nanoscale, 2016)
Tuning the band alignment is proved to be an effective way to facilitate carrier transportation and thus enhance the power conversion efficiency (PCE) of solar cells. Doping the compact layer with metal ions or modifying the interfaces among functional layers in perovskite solar cells (PSCs) can appreciably improve the PCE of PSCs. Inspired by the rare earth elemental doping of TiO , which has witnessed the success in photocatalysis and dye-sensitized solar cells, we firstly demonstrated here that La doping in the mesoporous TiO layer of a mesostructured PSC can tune its Fermi level and thus significantly enhance the device PCE. Systematic analysis reveals that doping La into TiO raises the Fermi level of TiO through scavenging oxygen and inducing vacancies, which subsequently increases the open circuit voltage and the fill factor while reducing the series resistance of the PSC using La -doped TiO as a mesoporous layer. As a result, a PCE of 15.42% is achieved, which is appreciably higher than the PCE of a device with undoped TiO (12.11%).